Principals’ Learning-Centered Leadership and Teacher Professional Learning: Modeling the Mediating Effects of Teachers’ Calculative, Relational, and Faith Trust - Rezaee, Marziyeh; Golshan, Mohammad; Sarkeshikian, Amir (Assessment and Practice in Educational Sciences, 2026)
Lifelong learning has become an indispensable aspect of the teaching profession. Despite the widespread acknowledgment of the profound influence of organizational working conditions on teacher learning, the Iranian context has witnessed a paucity of research thoroughly investigating their interactive impacts. To address this gap, this research sought to explore the effects of principals' learning-centered leadership (PLCL), mediated by calculative (CT), relational (RT), and faith trust (FT), on teacher professional learning (TPL) in Iran. The participant of this investigation consisted of 206 Iranian instructors of English as a Foreign Language. All individuals held a Master of Arts degree in TEFL. The sample included 141 male and 65 female, with ages ranging from 25 to 35 years and teaching experience spanning 5 to 10 years. The study employed a multi-scale valid and reliable questionnaire as a data-gathering tool. It contained 68 questions distributed across the five constructs, with each construct receiving its own five-point Likert scale. The Partial Least Squares (PLS) path modeling was utilized in this exploratory research for data analysis. The results indicated that PLCL exerted significant positive direct and indirect effects, through CT, RT, and FT, on TPL. Particularly, RT was most significant in driving TPL, followed by CT and FT. The practical implications are discussed.